Flooring

The flooring material with a cellulose-based surface coating layer addresses the issue of sock wear by enhancing anti-slip and anti-wear properties, offering a durable and visually appealing solution for resin flooring.

JP7618364B2Active Publication Date: 2025-01-21TOLI
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021160733
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-30
Publication Date
2025-01-21
Estimated Expiration
2041-09-30

AI Technical Summary

Technical Problem

Conventional resin flooring materials with wear-resistant particles, such as alumina, provide excellent anti-slip properties but cause rapid wear of socks due to their high hardness.

Method used

A flooring material with a surface coating layer containing ionizing radiation-curable resin and powdered cellulose, featuring an uneven surface with concave and convex portions, including elongated protrusions, to enhance anti-slip and anti-wear properties.

Benefits of technology

The flooring material achieves both excellent anti-slip and anti-wear properties while maintaining low gloss and providing a good texture, with improved resistance to fabric abrasion and reduced sock wear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618364000004
    Figure 0007618364000004
  • Figure 0007618364000005
    Figure 0007618364000005
  • Figure 0007618364000006
    Figure 0007618364000006
Patent Text Reader

Abstract

To provide flooring materials that are excellent in anti-slip and anti-fouling properties and also in anti-wear properties.SOLUTION: The flooring material of the present invention has a surface coating layer 2 containing an ionizing radiation-curable resin 5, and the surface coating layer 2 contains powdered cellulose 8. In the surface coating layer 2, fine protrusions 6 caused by the powdered cellulose 8 are formed.SELECTED DRAWING: Figure 10
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flooring material having excellent anti-slip and anti-wear properties. [Background technology]

[0002] 2. Description of the Related Art Conventionally, resin flooring materials have been laid on the floors of office buildings, commercial facilities, apartment buildings, ordinary houses, and the like. 2. Description of the Related Art In some cases, a coating film having abrasion-resistant particles dispersed therein is provided on the surface of a resin flooring material in order to improve the slip resistance. For example, Patent Document 1 discloses a flooring material in which a coating film of a synthetic resin material such as an acrylate-based material is mixed with wear-resistant particles such as alumina that are harder than the coating film. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-278005 A Summary of the Invention

[0004] The flooring material of Patent Document 1 has excellent anti-slip properties because the abrasion-resistant particles are exposed from the surface of the coating film. However, since the coating of the above flooring materials contains highly hard, wear-resistant particles such as alumina, it has been found that when people walk on the floor while wearing socks, the socks tend to wear out. [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a flooring material which is excellent in both slip resistance and wear resistance. [Means for solving the problem]

[0006] The flooring material of the present invention has a surface coating layer containing an ionizing radiation curable resin, and the surface coating layer contains powdered cellulose. The surface of the surface coating layer is formed in an uneven shape having recesses and protrusions, and the powdered cellulose is contained in the recesses and protrusions. .

[0007] A preferred flooring material of the present invention contains the powdered cellulose in an amount of 0.5% by weight to 20% by weight when the entire surface coating layer is taken as 100% by weight. The preferred flooring of the present invention is The powdered cellulose includes fibrous cellulose having a fiber length of 1 μm or more and 200 μm or less. . The preferred flooring materials of the present invention are ,before The convex portion includes a long protrusion having a first protrusion protruding beyond the concave portion, and two or more second protrusions formed on the first protrusion and protruding beyond the first protrusion. In a preferred flooring material of the present invention, the first protrusion portion is approximately elongated in a planar view with its major axis in one direction on the surface of the surface coating layer, and the two or more second protrusion portions are connected in the major axis direction of the first protrusion portion. Effect of the Invention

[0008] The flooring material of the present invention is excellent in anti-slip and anti-abrasion properties. Furthermore, the flooring material of the present invention is preferable because it has low gloss and easily gives a good texture to the viewer. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a plan view of the flooring material of the first embodiment. [Diagram 2] FIG. 7 is a plan view of a flooring material according to a second embodiment. [Diagram 3] FIG. 2 is a cross-sectional view showing a first example of a layer structure of a flooring material. [Figure 4] FIG. 4 is a cross-sectional view showing a second example of the layer structure. [Diagram 5] FIG. 4 is a cross-sectional view showing a third example of the layer structure. [Figure 6] FIG. 11 is a cross-sectional view showing a fourth example of the layer structure. [Figure 7] FIG. 11 is a cross-sectional view showing a fifth example of the layer structure. [Figure 8] FIG. 13 is a cross-sectional view showing a sixth example of the layer structure. [Figure 9] FIG. 4 is an enlarged reference plan view showing the surface of the surface coating layer. [Figure 10] FIG. 10 is a further enlarged cross-sectional view taken along line XX in FIG. 9 . [Figure 11]FIG. 10 is a further enlarged cross-sectional view taken along line XI-XI in FIG. 9 . [Figure 12] Image of the surface of the flooring material produced in Example 2. [Figure 13] Image of the surface of the flooring material produced in Example 4. [Figure 14] Image of the surface of the flooring material produced in Example 6. [Figure 15] Reference diagram of flooring surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will now be described with reference to the accompanying drawings. In this specification, the "surface" of a flooring material or the "surface" of any layer that constitutes it refers to the surface away from the floor surface on which the flooring material is installed, and the "back surface" refers to the opposite surface (the side closer to the floor surface). A plan view refers to a view of the flooring material from a direction perpendicular to the surface of the flooring material. In this specification, the term "approximately" has a meaning that includes the range acceptable in the technical field of the present invention. In this specification, a numerical range expressed as "not less than a lower limit value and not more than an upper limit value" can be set to "not less than an arbitrary lower limit value and not more than an arbitrary upper limit value" by selecting an arbitrary lower limit value and an arbitrary upper limit value. It should also be noted that the dimensions, such as thickness and size, in each drawing are different from the actual dimensions.

[0011] [Flooring Overview] The flooring material of the present invention has excellent anti-slip and anti-abrasion properties, and further has low gloss. Here, anti-slip property refers to the resistance to slipping when walking on the surface of the flooring material, etc., and abrasion resistance refers to the resistance to wear of items that come into contact with the surface of the flooring material (such items include clothing such as socks, footwear such as the soles of slippers, etc.).

[0012] FIG. 1 is a plan view of a flooring material 1 according to a first embodiment, and FIG. 2 is a plan view of a flooring material 1 according to a second embodiment. Referring to FIG. 1, the flooring material 1 is formed in a long strip shape in a plan view. The long strip refers to a generally rectangular shape in a plan view in which the length in the longitudinal direction is sufficiently longer than the short side direction, and for example, the length in the longitudinal direction is three times or more, preferably five times or more, of the length in the short side direction. Specific dimensions of the long strip include, for example, a short side length of 500 mm or more and 3000 mm or less, and a longitudinal length of 2 m or more and 500 m or less. The flooring material 1 formed in a long strip shape is usually wound in a roll for storage and transportation, and is cut into a desired shape at the construction site for use. Referring to Fig. 2, the flooring material 1 is formed in a sheet shape that is approximately square in plan view. However, the sheet-shaped flooring material 1 may be formed in a substantially rectangular or hexagonal shape in plan view (not shown). Specific dimensions of the flooring material 1 that is approximately square or rectangular in plan view are, for example, length x width = 200 mm to 1000 mm x 200 mm to 1000 mm. The sheet-shaped flooring material 1 as shown in the figure is stored and transported in a state where multiple sheets are stacked together or individually rolled up into a roll.

[0013] The flooring material 1 of the present invention may be flexible, or may be relatively hard without flexibility. The degree of flexibility of the flooring material 1 is, for example, such that the flooring material 1 can be wound in a roll around a core having a diameter of 10 cm with the back side of the flooring material 1 facing the core. The overall thickness of the flooring material 1 is not particularly limited and is, for example, from 0.5 mm to 10 mm, and preferably from 1 mm to 8 mm.

[0014] [Layer structure of flooring material] The flooring material 1 has a main body layer and a surface coating layer provided on the main body layer and containing an ionizing radiation curable resin and powdered cellulose. The main body layer has a surface layer having a protective layer, and preferably has the surface layer and a back layer provided on the back side thereof. The surface of the surface coating layer forms the outermost surface of the flooring material 1. Therefore, the flooring material 1 of the present invention does not have pile yarn or cloth on its surface, and the surface of the flooring material 1 is formed by the surface coating layer. Each layer that forms the flooring material 1 is firmly bonded to each other. The surface layer is a layer for imparting a design to the flooring material 1, and may be a single layer or multiple layers. When the surface layer is a single layer, a layer made of a resin to which a pigment has been added is used, and when the surface layer is multiple layers, a configuration having, in order from the surface side, a protective layer and a colored decorative layer is preferably used. When a colored decorative layer is provided on the surface layer, in order to make the color of the colored decorative layer visible from the surface of the flooring material 1, the surface coating layer or protective layer laminated on the surface side of the colored decorative layer is a colorless and transparent layer or a colored and transparent layer, preferably a colorless and transparent layer.

[0015] Fig. 3 shows a first example of the layer structure of the flooring material 1, and Figs. 4 to 8 show second to sixth examples of the layer structure of the flooring material 1. Figs. 3 to 8 are cross-sectional views taken along the line III-III in Figs. 1 and 2. The flooring material 1 in Fig. 3 has, in order from the surface side, a surface coating layer 2, a surface layer 3, and a back layer 4. The surface layer 3 has, in order from the surface side, a protective layer 31, a colored decorative layer 32, and a base layer 33. The back layer 4 has, in order from the surface side, a first resin layer 41, a second resin layer 42, and a third resin layer 43. The back layer 4 may have four or more resin layers. The flooring material 1 in FIG. 4 differs from the layer structure example in FIG. 3 in that the surface layer 3 is made up of only a protective layer 31 and a colored decorative layer 32 in that order from the surface side. The flooring material 1 in Fig. 5 differs from the layer structure examples in Fig. 3 and Fig. 4 in that the back layer 4 has a first resin layer 41 and a second resin layer 42. Note that Fig. 5 shows the layer structure shown in Fig. 3 as the surface layer 3, but the layer structure shown in Fig. 4 (consisting of a protective layer 31 and a colored decorative layer 32) may also be used. The same applies to the surface layer 3 in the other figures below. The flooring material 1 in FIG. 6 differs from the layer configuration examples in FIGS. 3 and 4 in that the back layer 4 is composed of only a first resin layer 41. The flooring material 1 in Fig. 7 differs from the other layer configuration examples in that the back layer 4 has a fiber layer 44 embedded in the resin layer, or a fiber layer (not shown) interposed between the back surface of the front layer 3 and the front surface of the back layer 4. The back layer 4 in Fig. 7 has, in order from the front surface side, a first resin layer 41, a fiber layer 44, and a second resin layer 42. Therefore, the fiber layer 44 in Fig. 7 is embedded inside the resin layer. The flooring material 1 in Fig. 8 differs from the other layer configuration examples in that a fiber layer 46 is provided on the back surface of the back layer 4. The back layer 4 in Fig. 8 has, in order from the front surface side, a first resin layer 41, one fiber layer 45, a second resin layer 42, and another fiber layer 46.

[0016] Although not shown, the layer configurations of the back layer 4 in Figures 3 to 8 may be appropriately combined or replaced. Also, although not shown, some layers of the back layer 4 may be omitted, or another functional layer may be added to the back layer 4. For example, an adsorption part or adhesive part may be provided on the back surface of the back layer 4 (or the back surface of the front layer 3 if there is no back layer 4) (not shown). The adsorption part or adhesive part is a part that adheres to the floor surface in a peelable manner. Examples of materials for forming the adsorption part include very soft foamed resins, and examples of materials for forming the adhesive part include peel-up adhesives.

[0017] The surface of the flooring material 1 may also be embossed with irregularities. The embossed irregularities refer to irregularities that can be visually identified. The embossed irregularities may be irregularities that form a specific pattern in appearance, or may be irregularities that do not form a specific pattern in appearance. Examples of the former include irregularities that represent a wood grain pattern and irregularities that represent a stone grain pattern. Examples of the latter include matte irregularities and sand-grained irregularities. When forming embossed irregularities on the surface of the flooring material 1, the depth of the irregularities is not particularly limited and is, for example, from 0.1 mm to 1 mm, and preferably from 0.2 mm to 0.5 mm. The depth of the embossed irregularities refers to the difference in height between the top of the convexity and the bottom of the concavity.

[0018] [Surface coating layer] The surface coating layer is a layer that constitutes the outermost surface of the flooring material. The surface coating layer includes an ionizing radiation curable resin and powdered cellulose. The ionizing radiation curable resin is a resin that is crosslinked and cured by irradiation with a charged particle beam or electromagnetic wave having an energy quantum capable of crosslinking and polymerizing a monomer, etc. (e.g., an electron beam, ultraviolet light, etc.) As the ionizing radiation curable resin, for example, a resin in which a curable monomer or oligomer is cured by ionizing radiation can be suitably used. The curable monomer or oligomer is not particularly limited as long as it is curable by ionizing radiation. As the curable monomer, one or more of monofunctional monomers, bifunctional monomers, or trifunctional or higher polyfunctional monomers can be used.

[0019] Examples of the curable monomer or oligomer include a monomer or oligomer having a polymerizable unsaturated bond group, such as a (meth)acrylate group or a (meth)acryloyloxy group, or an epoxy group in the molecule. Specific examples of the curable monomer include styrene-based monomers such as α-methylstyrene, methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, urethane (meth)acrylate, and polyol compounds having two or more thiol groups in the molecule. Specific examples of the curable oligomer include monofunctional (meth)acrylates or polyfunctional (meth)acrylates having a polymerizable unsaturated bond, such as urethane (meth)acrylate, polyester (meth)acrylate, epoxy (meth)acrylate, and organic-inorganic hybrid (meth)acrylate obtained by condensing colloidal silica and (meth)acryloylalkoxysilane, as well as unsaturated polyesters.

[0020] Among these, in the present invention, it is preferable to use urethane (meth)acrylate as the curable monomer or oligomer, since it has appropriate flexibility, excellent heat resistance, chemical resistance, durability, etc., and further excellent adhesion to the main body layer. Note that in the present invention, acrylate and methacrylate are collectively referred to as "(meth)acrylate", acrylic acid or methacrylic acid is collectively referred to as "(meth)acrylic acid", and acryloyl group or methacryloyl group is collectively referred to as "(meth)acryloyl group". The molecular weight of the curable monomer or oligomer is not particularly limited, but may be within the range of 200 to 10,000, for example.

[0021] In the present invention, a curable monomer or oligomer that is cured by ultraviolet light can be preferably used because it can form a relatively strong surface coating layer and is also versatile. That is, as the ionizing radiation curable resin, an ultraviolet curable resin can be preferably used. The ultraviolet curable resin is not particularly limited, and for example, unsaturated polyesters such as condensates of unsaturated dicarboxylic acids and polyhydric alcohols, polyester (meth)acrylates, polyether (meth)acrylates, polyol (meth)acrylates, melamine (meth)acrylates, epoxy (meth)acrylates, melamine (meth)acrylates, and the like can be used. These can also be commercially available products. The content of the ionizing radiation curable resin in the surface coating layer is not particularly limited, but is, for example, 30% by weight or more and 97% by weight or less, and more preferably 40% by weight or more and 70% by weight or less, when the entire surface coating layer is taken as 100% by weight. By having the content of the ionizing radiation curable resin in the above range, a surface coating layer with high hardness can be formed, and the stain resistance of the flooring material can be improved. Note that stain resistance refers to the ease of removing stains attached to the surface of the flooring material.

[0022] The powdered cellulose creates fine irregularities on the surface of the surface coating layer. Note that the fine irregularities refer to microscopic irregularities that are different from embossed irregularities. Fig. 9 is a plan view showing, for reference, an enlarged state of the surface of the surface coating layer 2, Fig. 10 is an enlarged cross-sectional view showing the surface coating layer 2 cut along a first direction, and Fig. 11 is a further enlarged cross-sectional view showing the surface coating layer 2 cut along a second direction. Note that Figs. 10 and 11 show only the surface coating layer 2 and the protective layer 31, and other layers such as a colored decorative layer are omitted.

[0023] As shown in Figs. 9 to 11, the surface of the surface coating layer 2 is formed in an uneven shape having a plurality of recesses 7 and protrusions 6. The recesses 7 and protrusions 6 are relative concepts, and the protrusions 6 are parts that protrude upward with respect to the recesses 7. The unevenness of the surface of the surface coating layer 2 forms a sea-island pattern with the recesses 7 as the sea and the plurality of protrusions 6 as the islands. The protrusions 6 are fine. The fine protrusions 6 include long protrusions 6A that have an elongated shape with the first direction as the major axis and the second direction as the minor axis in a plan view shown in the same figure. The first direction and the second direction are directions perpendicular to each other within the surface of the surface coating layer 2. The protrusions 6 also include long protrusions 6B that have an elongated shape in a plan view with the second direction as the major axis and the second direction as the minor axis. The term "long axis is in the first direction" or "long axis is in the second direction" means that the long axis of the long protrusion 6A or the long protrusion 6B is approximately parallel to the first direction or the second direction. The protrusion 6 includes a protrusion 6C that is approximately circular in plan view and a protrusion (not shown) that is irregular in plan view.

[0024] The long protrusions 6A and 6B each have a first protrusion 61 that protrudes beyond the recess 7, and two or more second protrusions 62 that are formed on the first protrusion 61 and protrude beyond the first protrusion 61. For example, the long protrusions 6A and 6B each independently have a major axis dimension of 200 μm or more and 1500 μm or less, and a minor axis dimension of 50 μm or more and 200 μm or less. The first protrusion 61 is in the form of a plateau rising on a flat surface, and the second protrusion 62 is in the form of a mountain rising further up on the plateau-like first protrusion 61. The two or more second protrusions 62 formed on the first protrusion 61 are connected to each other at intervals in the long axis direction. For the long protrusion 6A having the long axis in the first direction, two or more second protrusions 62 are arranged side by side in the first direction, and for the long protrusion 6B having the long axis in the second direction, two or more second protrusions 62 are arranged side by side in the second direction. By forming the long protrusions 6A having such first protrusions 61 and second protrusions 62 on the surface coating layer 2, it is possible to achieve both anti-slip properties and anti-abrasion properties. Furthermore, by forming the long protrusions 6A having two or more second protrusions 62 aligned in the first direction, it is possible to enhance anti-slip properties while maintaining anti-fouling properties.

[0025] As shown in Figs. 10 and 11, fine protrusions 6 such as long protrusions 6A are formed by the presence of powdered cellulose 8. Protrusions 6 are formed by a plurality of powdered cellulose 8 gathering and piling up. In some cases, protrusions 6 are formed by a single powdered cellulose 8. Furthermore, the surfaces of many of the protrusions 6 are covered with the ionizing radiation curable resin (in other words, the powdered cellulose 8 forming the protrusions 6 is covered with the ionizing radiation curable resin), but on the surfaces of some of the protrusions 6, the powdered cellulose 8 is partially exposed. In Fig. 9, for the sake of convenience, the first protrusions 61 are shaded and the second protrusions 62 are marked with numerous dots. In Fig. 10 and Fig. 11, the ionizing radiation curable resin 5 is marked with thin diagonal lines and the powdered cellulose 8 is left blank.

[0026] The surface roughness Sa (arithmetic mean height) of the surface coating layer is, for example, 0.1 μm to 5.0 μm, preferably 0.5 μm to 3.0 μm. The Sa is a parameter obtained by extending Ra (arithmetic mean height of lines) to a surface, and is measured, for example, in accordance with ISO 25178.

[0027] Powdered cellulose is a fine fibrous material made from wood such as conifers and broad-leaved trees; leaf, stem, or bark fibers of hemp, Mitsumata, paper mulberry, gampi, straw, bagasse, bamboo, and the like; seed hair fibers of cotton, Japanese quince, kapok, and the like; or a product obtained by partially hydrolyzing such fibers as required; or processed fibers such as cotton, hemp, and rayon.

[0028] The powdered cellulose may have a variety of shapes, including fibrous cellulose, granular cellulose which cannot be said to be fibrous, flat cellulose, and cellulose of an irregular shape whose shape cannot be particularly specified. The fiber diameter of the fibrous powdered cellulose is not particularly limited, and is, for example, 1 μm to 50 μm, and preferably 10 μm to 40 μm, and the fiber length is not particularly limited, and is, for example, 1 μm to 200 μm, and preferably 10 μm to 100 μm. If the fiber diameter and fiber length are equal to or greater than the lower limit, the anti-slip properties can be improved, and if they are equal to or less than the upper limit, the coating liquid can be applied well when forming the surface coating layer. For example, the powdered cellulose having an average fiber diameter of 30 μm to 40 μm and an average fiber length of 40 μm to 50 μm can be suitably used.

[0029] In the present invention, it is preferable that the surface coating layer contains powdered cellulose of various sizes. By containing powdered cellulose of various sizes, a plurality of fine convex portions having different protruding heights and protruding surface areas due to the powdered cellulose are formed in the surface coating layer, and therefore a surface coating layer with excellent anti-slip properties can be formed. For example, the surface coating layer contains powdered cellulose having a particle size (D50) of 35 μm or more and 45 μm or less at a cumulative frequency of 50% by volume in a volume-based particle size distribution. Preferably, the surface coating layer contains powdered cellulose having a particle size (D50) of 35 μm or more and 45 μm or less at a cumulative frequency of 50% by volume in a volume-based particle size distribution and a particle size (D90) of 130 μm or more and 140 μm or more at a cumulative frequency of 90% by volume. Powdered cellulose having such a particle size distribution can be obtained, for example, by sieving.

[0030] The particle size distribution of the powdered cellulose can be obtained from the surface coating layer. For example, the particle size distribution of the powdered cellulose contained in the surface coating layer can be obtained by taking an electron micrograph of the surface of the surface coating layer using a scanning electron microscope with an elemental analysis function such as an energy dispersive X-ray spectrometer, calculating the particle diameter (i.e., the circle equivalent diameter) by regarding the photographed particles as spherical with an approximate area, and measuring the particle diameter of any 100 powdered cellulose particles present in the photographed image. Then, the particle size distribution obtained using particle image analysis software from the measured particle size data of 100 particles with the vertical axis being frequency (%) and the horizontal axis being particle diameter (μm) can calculate the particle diameter (D50) at which the cumulative frequency is 50% by volume and the particle diameter (D90) at which the cumulative frequency is 90% by volume.

[0031] The content of powdered cellulose is not particularly limited. When a relatively large amount of powdered cellulose is contained, the ratio of fine convex parts to the surface area of ​​the surface coating layer increases, and a flooring material with excellent anti-slip properties can be formed. On the other hand, if the amount of powdered cellulose is too large, the coating liquid may not be applied well when the surface coating layer is formed. From this viewpoint, the content of powdered cellulose in the surface coating layer is, for example, 0.5% by weight or more and 20% by weight or less, and more preferably 3% by weight or more and 15% by weight or less, when the entire surface coating layer is taken as 100% by weight.

[0032] The thickness of the surface coating layer is not particularly limited and is, for example, from 5 μm to 50 μm, and preferably from 10 μm to 20 μm. The thickness T of the surface coating layer refers to the thickness at the recess 7 (see FIG. 10 for the thickness T). In addition, when the embossed unevenness is not formed on the surface of the flooring material (when the surface of the flooring material is substantially flat), in order to evenly impart the effect of the surface coating layer to the surface of the flooring material, it is preferable that the thickness of the surface coating layer is approximately the same in the surface direction of the flooring material. In addition, when the embossed unevenness is formed on the surface of the flooring material, the thickness of the surface coating layer may be different or approximately the same in the surface direction of the flooring material, but it is preferable that it is approximately the same for the same reason as above.

[0033] The surface coating layer contains an ionizing radiation curable resin and powdered cellulose, and may contain any compounding agent, if necessary, provided that the effect of the present invention is not impaired. Examples of the compounding agent include any aggregate, ultraviolet absorber, antistatic agent, stabilizer, antifungal agent, weathering stabilizer, surfactant, dispersant, thickener, plasticizer, preservative, rust inhibitor, antibacterial agent, antifreeze agent, antifoaming agent, and film-forming assistant. The content of such compounding agent added as necessary is not particularly limited, but is, for example, 3% by weight or less, and preferably 1% by weight or less, based on 100% by weight of the entire surface coating layer.

[0034] [surface] <Colored cosmetic layer> The colored decorative layer is a layer that imparts color to the flooring material. Examples of the colored decorative layer include a colored synthetic resin layer, a printed sheet, and a transfer sheet. The colored synthetic resin layer is a layer that itself exhibits color. The synthetic resin layer may be, for example, (1) a resin layer having the color of the resin itself, (2) a resin layer mixed with a colorant and colored by the colorant, or (3) a resin layer formed into a sheet by mixing colored resin chips. The colored decorative layer made of a colored synthetic resin layer is formed by laminating it on the surface of a base layer or a backing layer. A printing sheet is a synthetic resin sheet such as a vinyl chloride resin sheet on which ink is printed. A transfer sheet is obtained by printing and solidifying a printing ink on a substrate such as a release paper, and then peeling off the solidified printing ink. A colored decorative layer made of the transfer sheet is formed by transferring the colored decorative layer onto the surface of a substrate layer or the back surface of a protective layer. The thickness of the colored decorative layer is not particularly limited, but is, for example, 0.5 μm to 1 mm, and preferably 1 μm to 0.8 mm. When the colored decorative layer is made of a colored synthetic resin layer, the thickness is, for example, 0.3 mm to 1 mm, and when the colored decorative layer is made of a printing sheet or a transfer sheet, the thickness is, for example, 0.5 μm to 0.5 mm.

[0035] <Protective layer> The protective layer is a layer for protecting the colored decorative layer. The protective layer is colorless and transparent or colored and transparent, and is preferably colorless and transparent. The protective layer is made of a resin layer. The protective layer is preferably a non-foamed body. The resin component constituting the protective layer is not particularly limited, and examples thereof include vinyl chloride resins; polyolefin resins such as polyethylene and polypropylene; styrene resins such as polystyrene; and ester resins such as polyethylene terephthalate, and it is preferable to include vinyl chloride resins as the main component resin. Here, in this specification, the main component resin of a certain layer means a resin that occupies 60% by weight or more, preferably 80% by weight or more, and more preferably 90% by weight or more of the total resin components contained in the layer (when the total resin components are 100% by weight).

[0036] Vinyl chloride resins are polymers formed by polymerizing at least vinyl chloride monomer (chloroethylene). Vinyl chloride resins include not only homopolymers formed by homopolymerizing chloroethylene, but also copolymers of chloroethylene and other monomers that can be copolymerized with chloroethylene, mixtures of homopolymers and copolymers, and mixtures of two or more copolymers. The term "mixture" refers to a homopolymer and copolymer, or a polymer in which copolymers are kneaded together without substantially polymerizing. Examples of vinyl chloride resins include vinyl chloride polymers (homopolymers); chlorinated vinyl chloride; partially crosslinked vinyl chloride; copolymers containing vinyl chloride such as vinyl chloride-vinyl acetate copolymer, vinyl chloride-ethylene copolymer, vinyl chloride-propylene copolymer, vinyl chloride-styrene copolymer, vinyl chloride-isobutylene copolymer, vinyl chloride-vinylidene chloride copolymer, vinyl chloride-butadiene copolymer, vinyl chloride-isoprene copolymer, and vinyl chloride-chlorinated propylene copolymer; mixtures of homopolymers and one or more copolymers, and mixtures of two or more copolymers. Preferably, vinyl chloride polymers (homopolymers) are used. These vinyl chloride resins may be used alone or in combination of two or more.

[0037] The vinyl chloride polymer (homopolymer) may be one produced by an emulsion polymerization method, a suspension polymerization method, a solution polymerization method, a bulk polymerization method, or the like, and it is preferable to use a paste vinyl chloride resin and / or a suspension vinyl chloride resin. The vinyl chloride paste resin is, for example, a vinyl chloride paste obtained by emulsion polymerization, and the viscosity can be adjusted appropriately by a plasticizer. The vinyl chloride paste resin is a fine powder consisting of a large number of fine particle aggregates with a particle diameter of 0.1 to 10 μm (preferably 1 to 3 μm), and preferably the surface of the fine powder is coated with a surfactant. The average degree of polymerization of the vinyl chloride paste resin is preferably about 1000 to 2000. The suspension vinyl chloride resin is, for example, a vinyl chloride resin obtained by suspension polymerization. The suspension vinyl chloride resin is a fine powder with a particle size of preferably 20 μm or more and 100 μm or less. The average polymerization degree of the suspension vinyl chloride resin is preferably about 700 or more and 1500 or less, more preferably about 700 or more and 1100 or less, and even more preferably about 700 or more and 1000 or less.

[0038] When the protective layer contains a vinyl chloride resin as a main component resin, the protective layer may contain a plasticizer and any suitable additive. Examples of the plasticizer include polyester plasticizers, glycerin plasticizers, polycarboxylic acid ester plasticizers, and polyalkylene glycol plasticizers. The additives may be any known additive, such as fillers, colorants, flame retardants, stabilizers, antioxidants, lubricants, antibacterial agents, antifungal agents, and surfactants. Examples of the fillers include calcium carbonate, titanium oxide, calcium oxide, barium carbonate, magnesium hydroxide, aluminum hydroxide, clay, talc, and mica.

[0039] The protective layer contains, for example, 30 parts by weight to 70 parts by weight of a plasticizer and 0.1 parts by weight to 20 parts by weight of an additive, relative to 100 parts by weight of a vinyl chloride resin. The thickness of the protective layer is not particularly limited, and is, for example, from 0.05 mm to 2 mm, and preferably from 0.1 mm to 1 mm. The protective layer may or may not contain a filler such as calcium carbonate, but from the viewpoint of forming a protective layer having excellent durability, it is preferable that the protective layer is substantially free of a filler.

[0040] <Base material layer> The base material layer is provided as necessary. The base material layer is made of a synthetic resin. The base material layer may be a foamed material that is foamed, or may be a non-foamed material that is not foamed. The resin component of the base layer is not particularly limited, and a conventionally known resin can be used. Generally, a thermoplastic resin is used, and furthermore, a soft thermoplastic resin is used. Examples of the thermoplastic resin include vinyl chloride resins; polyolefin resins; urethane resins; vinyl acetate resins such as ethylene-vinyl acetate copolymers; acrylic resins such as ethylene-methacrylate resins; polyamide resins; ester resins; various elastomers such as olefin elastomers and styrene elastomers; and rubber. These can be used alone or in combination of two or more. Since it is inexpensive, has excellent flexibility and durability, and further adheres firmly to the back layer, it is preferable that the base layer contains a vinyl chloride resin as a main component resin. When the resin layer of the back layer contains a vinyl chloride resin as a main component resin, it contains, for example, a vinyl chloride resin, a plasticizer, and a filler, and contains various additives as necessary. As the vinyl chloride resin, plasticizer, and filler of the resin layer, those described in the above <Protective Layer> section are used.

[0041] [Back layer] <Resin layer> The resin layers of the backing layer, such as the first resin layer, the second resin layer, and the third resin layer, are layers that mainly constitute the strength and weight of the flooring material. The resin layers may be foamed or non-foamed. When the backing layer has multiple resin layers, at least one resin layer may be made of a foam and at least one resin layer may be made of a non-foamed material, or all of the resin layers may be made of a foam or a non-foamed material. When the backing layer has multiple resin layers, the main component resins of each resin layer may be different, or the main component resins of each resin layer may be the same. The resin component of the resin layer is not particularly limited, and may be a conventionally known one, for example, the one described in the above section of <Base layer>. The resin layer of the back layer preferably contains a vinyl chloride resin as a main component resin, since it is inexpensive, has excellent flexibility and durability, and further strongly adheres to the surface layer. When the resin layer of the back layer contains a vinyl chloride resin as a main component resin, it contains, for example, a vinyl chloride resin, a plasticizer, and a filler, and contains various additives as necessary. The vinyl chloride resin, plasticizer, and filler of the resin layer may be the one described in the above section of <Protective layer>.

[0042] <Fiber layer> The fiber layer of the back layer is provided for the purpose of maintaining the dimensional stability of the flooring material. Examples of the fiber layer include nonwoven fabric and woven fabric. The material of the fiber constituting the nonwoven fabric or woven fabric is not particularly limited, and examples thereof include synthetic resin fibers such as polyester and polyolefin; inorganic fibers such as glass and carbon; and natural fibers. In particular, it is preferable to use a glass sheet containing glass fiber as the fiber layer, since the dimensional change due to temperature is small.

[0043] [Flooring manufacturing method] The flooring material of the present invention can be produced by the following production method, but the flooring material of the present invention is not limited to those produced by the following production method. The method for manufacturing a flooring material includes a step of forming a main body layer and a step of forming a surface coating layer on the surface of the main body layer. When manufacturing a flooring material having an embossed unevenness on its surface, the method includes a step of forming a main body layer, a step of embossing the surface of the main body layer, and a step of forming a surface coating layer on the surface of the main body layer having the unevenness formed by embossing. In the following, a simple explanation will be given by taking as an example a case where the main layer is composed of a front layer and a back layer.

[0044] <Main layer formation process> As explained in the above section [Layer structure of flooring material], various combinations of layers are possible for the surface layer. According to the surface layer to be formed, a protective layer, a colored decorative layer, etc. are prepared. For example, a resin sheet formed into a film can be used as the protective layer. In the case of a protective layer whose main resin component is vinyl chloride resin, as explained in the above section <Protective layer>, a resin sheet is obtained by mixing vinyl chloride resin, plasticizer, filler, etc., and forming it into a film. Also, for example, a printed sheet is used as the colored decorative layer. As explained in the above section [Layer structure of flooring material], various combinations of layers are possible for the back layer. Prepare a resin layer or a fiber layer according to the back layer to be formed. For example, a resin sheet formed into a film can be used as the resin layer. In the case of a resin layer whose main resin component is vinyl chloride resin, a vinyl chloride resin, a plasticizer, a filler, etc. are mixed and formed into a film to obtain a resin sheet.

[0045] A laminate is formed by stacking a resin sheet or a printed sheet forming a surface layer, and then stacking a resin sheet or a fiber layer forming a back layer, in order from the surface side. The laminate is heated to bond adjacent sheets and layers to obtain a main layer. When vinyl chloride resin is the main component, the heating temperature is equal to or higher than the temperature at which vinyl chloride resin melts, for example, 140°C or higher and 200°C or lower. In order to bond the layers more firmly, it is preferable to pressurize the laminate. The pressing method is not particularly limited, and examples include a pressure roller and a press plate.

[0046] <Embossing process> By pressing an embossing roller or an embossing plate against the surface of the laminate, embossed irregularities are formed on the surface of the laminate. When performing embossing such as pressing with an embossing roller, it is preferable to heat at least the surface of the laminate. The heating may involve heating the laminate before embossing and / or simultaneously with embossing. An example of the latter is the use of a heated embossing roller.

[0047] <Surface coating layer forming process> A coating liquid containing an ionizing radiation curable resin (or a curable monomer or oligomer capable of forming an ionizing radiation curable resin), powdered cellulose, and compounds added as necessary is applied to the surface of the above laminate (surface of the protective layer) to form a coating film, and the coating film is cured, thereby forming a surface coating layer. The ionizing radiation curable resin, powdered cellulose and compounding materials may be the same as those explained in the above section on [Surface coating layer].

[0048] In preparing the coating liquid, a radical polymerization initiator may be added as necessary. The radical polymerization initiator is a compound that generates radicals by irradiation with ionizing radiation, and one or more of known hydrogen abstraction or photocleavage types can be used. Such radical polymerization initiators can also be used in combination with photosensitizers as necessary. The radical polymerization initiator is not particularly limited, and examples thereof include 2,2-dimethoxy-2-phenylacetophenone, acetophenone, benzophenone, xanthone, 3-methylacetophenone, 4-chlorobenzophenone, 4,4'-dimethoxybenzophenone, benzoin propyl ether, benzyl dimethyl ketal, N,N,N',N'-tetramethyl-4,4'-diaminobenzophenone, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, and thioxanthan compounds. The coating solution can be prepared by mixing these components substantially uniformly. The mixing is preferably carried out until the powdered cellulose is sufficiently dispersed.

[0049] The method for applying the coating liquid is not particularly limited, and various coater methods can be used, such as a roll coater, a blade coater, a knife coater, a curtain coater, etc. For example, by applying the coating liquid while applying a tensile force in one direction (for example, a first direction) using the coater method, a surface coating layer having elongated convex portions as shown in FIG. The uncured coating film is cured by irradiating the coating film with ionizing radiation. As the ionizing radiation, electromagnetic waves or charged particles having energy capable of curing the coating film may be used. For example, ultraviolet light or an electron beam may be used. Examples of ultraviolet light sources include low pressure mercury lamps, medium pressure mercury lamps, high pressure mercury lamps, extra-high pressure mercury lamps, halogen lamps, carbon arc lamps, metal halide lamps, xenon lamps, black lights, nitrogen lasers, electron beam accelerators, and sources of radioactive elements. The amount of ionizing radiation may be appropriately set depending on, for example, the type of monomer or oligomer used, and may be, for example, 50 mJ / cm2 in terms of the integrated light amount at an ultraviolet wavelength of 365 nm. 2 More than 5000mJ / cm 2 The following are some examples: In this way, a flooring material can be obtained in which a surface coating layer is formed on the surface of the main body layer (surface of the protective layer).

[0050] [Use of flooring materials] The flooring material of the present invention can be used as a flooring material for buildings, etc. The flooring material of the present invention can also be used as a waist wall material. The flooring material is laid on a floor surface via an adhesive or pressure sensitive adhesive. However, if an adhesive portion is provided on the back surface of the flooring material of the present invention, it can be laid on the floor surface as it is without using an adhesive or pressure sensitive adhesive. The flooring material of the present invention can be used, for example, indoor floor surfaces in commercial facilities such as stores and hotels, office buildings, general residential buildings, etc., and outdoor floor surfaces in their passageways, verandas, etc. In particular, since the flooring material of the present invention has excellent anti-slip and anti-abrasion properties, it can be suitably used as a flooring material for floor surfaces that come into direct contact with clothing such as socks, for example, indoor floor surfaces in commercial facilities such as hotels and general residential buildings. EXAMPLES

[0051] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0052] [Materials used] ·Ionizing radiation curable resin Urethane-based ultraviolet-curing resin (product name "Orex No. 171 Matte" manufactured by Chugoku Paint Co., Ltd. Solvent-free liquid type). Powdered cellulose The product name of the product manufactured by Rettenmaier is "ARBOCEL FD600-30". In sieve analysis, all particles of this product are smaller than 71 μm, with 7% larger than 45 μm. Sieve analysis is performed using an air jet sieve in accordance with DIN EN ISO 4610. ·alumina Product name "AW15-20" manufactured by Nippon Steel Chemical & Material Co., Ltd. Spherical. Average particle size 15.5±2.0μm.

[0053] · First PVC sheet A first resin sheet was placed on the base fabric, a second resin sheet was placed on the first resin sheet, and the sheets were heated and fused to produce a first polyvinyl chloride sheet consisting of a second resin layer / a first resin layer / a base fabric in that order from the surface side. The second resin layer corresponds to the surface layer of the main body layer, and the first resin layer and the base fabric correspond to the back layer of the main body layer. The base fabric was a woven fabric made of a mixture of polyethylene terephthalate and cellulose fibers. The thickness of this first polyvinyl chloride sheet was about 2 mm. The first resin sheet is composed of 58% by weight of vinyl chloride resin, 19% by weight of plasticizer (bis(2-ethylhexyl) phthalate), 19% by weight of filler (calcium carbonate), and 4% by weight of stabilizer, etc. The second resin sheet is composed of 20% by weight of vinyl chloride resin, 15% by weight of plasticizer (bis(2-ethylhexyl) phthalate), 62% by weight of filler (calcium carbonate), and 3% by weight of stabilizer, etc.

[0054] ·Second PVC tile The third resin sheet, the fourth resin sheet, and the fifth resin sheet were produced using a calendar molding machine. The third resin sheet, the fourth resin sheet, the fifth resin sheet, the printed sheet, and the protective sheet were stacked and heated to fuse them together, and then the surface was embossed and punched into a square shape in plan view to produce a second polyvinyl chloride tile consisting of a protective layer / printed layer / fifth resin layer / fourth resin layer / third resin layer in this order from the surface side. The protective layer and the printed layer correspond to the surface layer of the main body layer, and the third resin layer to the fifth resin layer correspond to the back layer of the main body layer. The thickness of this second polyvinyl chloride tile was about 3 mm. The third resin sheet is made of 35% by weight of vinyl chloride resin, 11% by weight of plasticizer (bis(2-ethylhexyl) phthalate), 54% by weight of stabilizer, etc. The fourth resin sheet is made of 21% by weight of vinyl chloride resin, 9% by weight of plasticizer (bis(2-ethylhexyl) phthalate), 70% by weight of stabilizer, etc. The fifth resin sheet is made of 25% by weight of vinyl chloride resin, 8% by weight of plasticizer (bis(2-ethylhexyl) phthalate), 67% by weight of stabilizer, etc. The print sheet is made of 80% by weight of vinyl chloride resin, 10% by weight of plasticizer (bis(2-ethylhexyl) phthalate), 10% by weight of stabilizer, etc. The protective sheet is composed of 75% by weight of vinyl chloride resin, 19% by weight of plasticizer (bis(2-ethylhexyl) phthalate), and 6% by weight of stabilizer.

[0055] [Example 1] The powdered cellulose was added to the ionizing radiation curable resin and mixed for about 5 minutes using a hand mixer to prepare a coating liquid containing 1% by weight of powdered cellulose. This coating liquid was applied to the surface of the first vinyl chloride sheet in a uniform thickness using a sponge roll, and then immediately irradiated with ultraviolet light from an arc ultraviolet lamp in the air to harden the coating, forming a surface coating layer with a thickness of about 15 μm. In this way, a flooring material consisting of a surface coating layer / first vinyl chloride sheet was produced. The thickness of the surface coating layer was measured at a portion not having fine protrusions.

[0056] [Examples 2 to 7] A surface coating layer having a thickness of about 15 μm was formed in the same manner as in Example 1, except that the content of the powdered cellulose was changed to that shown in Table 1.

[0057] [Comparative Example 1] A surface coating layer having a thickness of about 15 μm was formed in the same manner as in Example 1, except that the powdered cellulose was not mixed.

[0058] [Comparative Example 2] A surface coating layer having a thickness of about 15 μm was formed in the same manner as in Example 1, except that alumina was used instead of powdered cellulose and a coating liquid was prepared with an alumina content of 5 wt %.

[0059] [Comparative Example 3] A surface coating layer having a thickness of about 15 μm was formed in the same manner as in Comparative Example 2, except that the alumina content was changed to 15% by weight.

[0060] [Surface roughness] The surface roughness Sa of the surface coating layer of the flooring materials obtained in Examples 1 to 7 and Comparative Examples 1 to 3 was measured. The surface roughness Sa was measured using a laser microscope VK-X3000 manufactured by Keyence Corporation under the following conditions. The surface roughness Sa was calculated as the arithmetic mean value of one measurement (n=1). Measurement mode: Laser confocal. Objective lens: 20X ·Measurement area: 3177μm x 2383μm.

[0061] [Anti-slip test - walking test] For the flooring materials obtained in Examples 1 to 7 and Comparative Examples 1 to 3, people (12 adult males and 3 adult females) walked on the surface of the dry flooring material (surface of the surface coating layer) while wearing socks, and each person evaluated the degree of slipperiness. Next, they took off their socks and walked barefoot in the same manner, and each person evaluated the slipperiness. The evaluation was performed by comparing Comparative Example 1 with Examples 1 to 7 and Comparative Examples 2 and 3. Specifically, the floor material of Comparative Example 1 was first walked on and the slipperiness at that time was evaluated. Next, the floor materials of Examples 1 to 7 and Comparative Examples 2 and 3 were walked on and the slipperiness of those floor materials was evaluated in comparison with the floor material of Comparative Example 1 when walking. The slipperiness of Comparative Example 1 was fixed as point 5, and when each person was able to evaluate it as less slippery than Comparative Example 1, points 6 to 10 were given in increments of 1 according to the degree, and when each person was able to evaluate it as more slippery than Comparative Example 1, points 4 to 1 were given in increments of 1 according to the degree. The higher the point, the less slippery it was, and the lower the point, the more slippery it was evaluated. The results are shown in Table 1. However, the results in Table 1 are the average points given by each person (rounded off to the nearest decimal place) except for Comparative Example 1. Although Example 1 and Comparative Example 1 in Table 1 received the same number of points, the majority of people felt that Example 1 was less slippery than Comparative Example 1.

[0062] It can be seen that the flooring materials of Examples 1 to 7 are less slippery than the flooring material of Comparative Example 1. In particular, the flooring materials of Examples 2 to 7, which contain 3% to 20% by weight of powdered cellulose, have excellent anti-slip properties. From these results, it can be said that a flooring material with excellent anti-slip properties can be obtained by adding approximately 2% or more by weight of powdered cellulose.

[0063] [Wear resistance test] The flooring materials obtained in Examples 1, 5 to 7 were left to stand for 24 hours under an environment of 23°C ± 2°C and humidity 50% RH ± 10% RH. Then, under the same environment, a surface friction strength tester was used to place a sliding piece with a woven fabric attached under a rubber piece on the surface of the flooring material (surface of the surface coating layer), and rubbed back and forth for about 45 cm under a load of 1000 g, and the number of reciprocations until the woven fabric was worn out was measured. The woven fabric was 40-number cotton broadcloth, and the rubber piece was cylindrical with a diameter of 20 mm and a height of 4 mm. The number of reciprocations until the woven fabric was worn out was determined by stopping the operation every 100 reciprocations (100 times) and checking the state of the woven fabric. Measurements were performed up to 3000 reciprocations (3000 times). The results are shown in Table 1.

[0064] [Gloss measurement] The flooring materials obtained in Examples 1 to 7 and Comparative Examples 1 to 3 were left to stand for 24 hours in an environment of 23°C ± 2°C and humidity 50% RH ± 10% RH. Then, in the same environment, the gloss of the surface of these flooring materials (surface of the surface coating layer) was measured using a gloss meter (product name "VG2000" manufactured by Nippon Denshoku Industries Co., Ltd.). The results are shown in Table 1. It can be seen that the flooring materials of Examples 1 to 7 have a lower gloss than the flooring material of Comparative Example 1. It is presumed that this low gloss is due to the fine irregularities formed in the surface coating layer by blending powdered cellulose in the surface coating layer. In particular, the flooring materials of Examples 3 to 7, which contain 5% by weight or more and 20% by weight or less of powdered cellulose, are excellent in low gloss.

[0065] [Anti-stain test - Tokyo Institute of Technology stain test] For the floor materials obtained in Examples 1 to 7 and Comparative Examples 1 to 3, dirt was attached to the surface (surface of the surface coating layer) according to the Tokyo Institute of Technology dirt test method, and the dirt was then wiped off and the dirt level of the surface of the floor material was evaluated. Similarly, the dirt level of the surface of the floor material was evaluated after wiping with a cloth soaked in water (after wiping with water). The specific test method is as follows. Each flooring material was cut into a rectangular shape of length x width = 15 cm x 15 cm to prepare a sample. A part of the surface of the surface coating layer of this sample was exposed and covered with a protective film (i.e., a part of the surface of the surface coating layer was formed as a blank to which dirt does not adhere). The surface of the sample opposite to the surface of the surface coating layer was attached to the inner side wall of a regular hexagonal column-shaped hollow container (each of the six sides of the hexagonal column had a length (axial direction) x width (circumferential direction) = 16.0 cm x 16.3 cm) of a rotary tester (manufactured by Yasuda Seiki Co., Ltd., product name: Tokyo Institute of Technology Soil Tester) using double-sided tape. 150 g of silicon carbide (No. 80) and 2 g of powdered pastel were placed in this hollow container, and the container was rotated clockwise and counterclockwise for a total of 3 minutes (rotation speed: 20 rotations / min).

[0066] After the rotation had stopped, the sample was removed from the container, and the surface of the surface coating layer that was not covered with the protective film was wiped with a dry cloth to remove dirt. The color difference between the surface after wiping with the cloth and the surface with the protective film removed (blank surface) was measured using a color difference meter (product name "ZE-2000" manufactured by Nippon Denshoku Industries Co., Ltd., measuring diameter 30 mmφ, double beam method using 0°-d method). The Y value was calculated from the color difference according to the following formula, and the Z value was calculated from the Y value. Formula (1): Color difference ΔE={(L-L1) 2 -(a-a1) 2 -(b-b1) 2} 1 / 2 Formula (2): Y value = 0.6531 x ΔE-0.4333 Formula (3): Z value = 0.2581 × Y value + 1.4493 Here, L indicates the brightness of the blank surface, L1 indicates the brightness of the surface after wiping with a cloth, a indicates the green to red color of the blank surface, a1 indicates the green to red color of the surface after wiping with a cloth, b indicates the blue to yellow color of the blank surface, and b1 indicates the blue to yellow color of the surface after wiping with a cloth.

[0067] Another sample was placed in a container and stained in the same manner as above, and then the surface of the surface coating layer not covered with the protective film was wiped with a cloth moistened with water to remove the stain. The color difference between the surface after wiping with water and the surface from which the protective film was removed (blank surface) was measured with a color difference meter in the same manner as above, and the Y value was calculated from the color difference according to the above formula, and the Z value was calculated from the Y value. However, "after wiping with cloth" in L1, a1, and b1 in the above formula should be read as "after wiping with water." The Z value is defined in a paper by Eiji Ono of the Tokyo Institute of Technology ("Research into stains on building floor finishing materials and their evaluation methods (2)" on pages 337 and 338 of the Abstracts of the Academic Lecture at the Architectural Institute of Japan's Annual Meeting in September 1980). The evaluation based on the Z value is as shown in Table 1. When the Z value is 4 or less, it can be evaluated that the stain is easy to remove.

[0068] The stain-resistant properties of the flooring materials of Examples 1 to 7 are difficult to rank compared to those of the flooring materials of Comparative Examples 1 to 3, and it is clear that the stain-resistant properties are not reduced even when powdered cellulose is added to the surface coating layer.

[0069] [Table 1]

[0070] [Surface texture evaluation] The unevenness and stickiness of the surfaces (surfaces of the surface coating layers) of the flooring materials obtained in Examples 1 to 7 and Comparative Examples 1 to 3 were evaluated by two people (one adult male and one adult female) in an environment of 23°C ± 2°C and humidity of 50% RH ± 10% RH. The results are shown in Table 2. ·Unevenness evaluation The surface of the flooring material was traced with a finger and evaluated for the presence or absence of irregularities and the feel thereof. Stickiness rating The entire palm of the hand was pressed against the surface of the flooring material for 30 seconds, and in this state the palm was moved back and forth several times in the direction of the surface in an area of ​​about 1 to 2 cm to evaluate the stickiness. Stickiness is the sensation that the surface of the flooring material clings to the skin due to sweat or moisture, and is particularly uncomfortable in the summer when temperatures are high.

[0071] It was confirmed that the more the amount of powdered cellulose was increased, the more unevenness was formed in the flooring materials of Examples 1 to 7. The flooring materials of Comparative Examples 2 and 3 did not have much unevenness, which is presumably because the alumina was sunk into the surface coating layer. In addition, the flooring materials of Examples 1 to 7 had no or almost no sticky feeling, but the flooring materials of Comparative Examples 1 to 3 had a sticky feeling. This is presumably due to the formation of fine irregularities on the surface coating layer of the flooring materials of the Examples and the material aspect that the irregularities are formed from powdered cellulose.

[0072] [Table 2]

[0073] [Imaging] The surface of the surface coating layer of the flooring material of Example 2, Example 4, and Example 6 was captured by using a laser microscope VK-X3000 manufactured by Keyence Corporation, with the measurement mode set to laser confocal and magnified 20 times to obtain a plurality of images, and then 25 of the images were linked by an image linking application (version 3.3.1.0) attached to the laser microscope VK-X3000, and further image processing was performed. Image processing was performed by a multi-file analysis application (version 3.2.0.66) attached to the VK-X3000. The image processing in the multi-file analysis application was performed by the following processes (1) to (4) in the image processing tool in sequence. (1) Height cut level of the image processing tool: Medium, (2) Surface shape correction of the same tool: Waviness removal Correction strength 5, (3) Surface shape correction of the same tool: Waviness removal Correction strength 5, (4) Reference surface setting of the same tool: Area designation Continuous surface extraction. The obtained image was set to an arbitrary color palette to obtain a color image with improved visibility. The images of the surfaces of the surface coating layers of Examples 2, 4, and 6 thus obtained are shown in Figures 12 to 14. The images obtained were in color, but Figures 12 to 14 have been converted to grayscale. The dimensions of the images in Figures 12 to 14 in the lateral direction on the paper are all about 3000 μm. Fig. 15 is a reference diagram for explaining the three-dimensional structure of the surface that was analyzed from the image. In Fig. 15, some of the parts corresponding to the above-mentioned long protrusions 6A, long protrusions 6B, protrusions 6C, first protrusions 61, second protrusions 62, and recesses 7 are given their corresponding reference numerals.

[0074] [Examples 8 to 14] Flooring materials of Examples 8 to 14 were produced in the same manner as in Examples 1 to 7, except that the first polyvinyl chloride sheet was replaced with a second polyvinyl chloride tile.

[0075] [Comparative Examples 4 to 6] Flooring materials of Comparative Examples 4 to 6 were produced in the same manner as in Comparative Examples 1 to 3, except that the first vinyl chloride sheet was replaced with a second vinyl chloride tile.

[0076] [Wear resistance test] The floor materials of Examples 8, 10, 13 and 14 and Comparative Examples 4 to 6 were subjected to the abrasion resistance test in the same manner as above. The results are shown in Table 3. It is seen that the flooring materials of Comparative Examples 5 and 6, which contain alumina, wear out the fabric early and are prone to wear. It is seen that the flooring materials of the Examples have excellent abrasion resistance. The abrasion resistance test results of the flooring materials of Examples 1, 5 to 7 and Examples 8, 10, 13 and 14 show that the abrasion resistance tends to decrease in proportion to the powdered cellulose content. Considering these results, it can be said that a flooring material with particularly excellent abrasion resistance can be obtained by adding about 15% by weight or less of powdered cellulose.

[0077] [Table 3] [Explanation of symbols]

[0078] 1. Flooring 2 Surface coating layer 3 Surface layer 4 Lining 5 Ionizing radiation curable resin 6 Convex 6A Long protrusion 61 1st protrusion 62 2nd protrusion 7 Recess 8. Powdered Cellulose

Claims

1. A surface coating layer containing an ionizing radiation curable resin, The surface coating layer comprises powdered cellulose, A flooring material, wherein the surface of the surface coating layer is formed unevenly having recesses and protrusions, and the powdered cellulose is contained in the recesses and protrusions.

2. 2. The flooring material according to claim 1, wherein the powdered cellulose is contained in an amount of 0.5% by weight to 20% by weight, when the entire surface coating layer is taken as 100% by weight.

3. A flooring material as described in claim 1 or 2, wherein the powdered cellulose includes fibrous cellulose having a fiber length of 1 μm or more and 200 μm or less.

4. A flooring material as described in any one of claims 1 to 3, wherein the convex portion includes a long protrusion portion having a first protrusion portion protruding further than the concave portion, and two or more second protrusion portions formed on the first protrusion portion and protruding further than the first protrusion portion.

5. The flooring material described in claim 4, wherein the first protrusion portion is approximately elongated in a planar view with its long axis extending in a first direction on the surface of the surface coating layer, and the two or more second protrusion portions are connected in the long axis direction of the first protrusion portion.

Citation Information

Patent Citations

  • Top plate for furniture

    JP1998327959A

  • Non-slip flooring material

    JP2007278005A

  • Decorative sheet

    JP2009029089A

  • Active energy ray-curable coating composition

    JP2020084116A

  • Active energy ray-curable resin composition

    JP2021020994A